PENINGKATAN KAPASITAS KEWIRAUSAHAAN MELALUI PELATIHAN OLAHAN KERIPIK PISANG BAGI KELOMPOK WANITA TANI DI DESA SOMONGARI - Nurul Putrie Utami; Hadi Sasongko; Zuchrotus Salamah; Purwanti Pratiwi Purbosari (Universitas Mataram, 2022)
Somongari Village is a village located in Kaligesing District, Purworejo whose main income is from durian and mangosteen plantations. However, in the last three years, plantation yields have continued to decline and so have the incomes of the people. Somongari Village actually has other plantation products in the form of bananas and is only sold at low prices which can be processed into processed products of high economic value and can become products that can be sold and increase the economy when the mangosteen and durian yields recede. This service activity aims to increase entrepreneurial capacity through training in making chocolate banana chips until they are ready to be marketed along with training in calculating the cost of sales(HPP) of banana chips. The target of this training activity was 14 members of the Suka Karya Makmur Women Farmers Group (KWT). The training media are presentation slides, leaflets, cooking utensils, kitchen scales and ingredients for making banana chips. Activities were carried out using demonstration and simulation methods. Training on banana chips processing was attended by very enthusiastic and active training participants. However, on the topic of HPP calculation, it is a new knowledge for participants, so the explanation was carried out slowly. So far, the determination of the selling price only considers the price of raw materials and did not involve aspects such as labor and equipment depreciation costs. With this training, it was found that there was an increase in knowledge about how to process banana chips and HPP (p = 0.025). Skills in processing chips until they are ready for sale are also getting better. Through this training, participants could improve their entrepreneurial skills by setting a selling price so they can get maximum profit. Product processing training along with HPP training can improve participants' knowledge and skills. This can increase the entrepreneurial capacity as well as the economic status of the community.